Green School-Based Animation Video Media In Increasing Student's Awareness Of The Environment - Erma Suryani Sahabuddin; Gufran Darma Dirawan (International Journal of Elementary Education, 2022)
Problems with the school environment will be much reduced if students have concerns about the school environment. Students' concern for the environment must be instilled from an early age so that it can be formed from the beginning of receiving an education so that they become more caring and respectful of the environment. Therefore, this research is a classroom action research that aims to analyze the use of green school-based animated video media to increase students' awareness of the environment. The approach used is qualitative. The research subjects were teachers and third-grade students, totaling 20 people. Data collection uses the format of observation, tests, and documentation. The data analysis technique used is descriptive qualitative and quantitative analysis. The results showed an increase in learning in the use of green school-based animated video media, both in the activities of teachers and students, as well as students' concern for the school environment. This study concludes that teacher-teaching activities and student-learning activities have increased. So that this research can help teachers in choosing media to stimulate students' thinking in increasing environmental awareness.